Microbound diet (MBD) can replace the use of l live feeds in larvae culture: A boon for fish larval nutrition : Microbound diet essentially required in larvae culture - Kumar, Sikendra; Das, Arabinda; Patel, Anusha; Mannur, Vijaykumar S; Kalyani, Rohini; Tanmoy Kumar Manna; Mohanta, Kedar Nath (Journal of Indian Fisheries Association, 2023)
Successful aquaculture mainly depends on the provision of quality seed and feed. Initial stage of larval rearing is very delicate and critical, and due to improper supply of nutritional balanced feed, their survival gets affected. Live feeds are used during initial rearing, but they are sometimes not nutritionally balanced, and they require a separate set-up and expertise for their mass production. Microparticulate diets can be an ideal solution to overcome this constraint; hence, they can be used along with the live feeds for the culture of fish larvae. The different microparticulate diets, such as microbound (MBD), microcoated (MCD), and microencapsulated (MED) diets, can be used to partially or completely substitute the live feeds in fish larval rearing, but among the three, the production of MBD is comparatively easier. The quality MBD can be prepared as a dry type using a suitable binder matrix. The binders used in the MBD are: sodium alginate, carrageenan, zein, gelatin, etc. These binders reduce the leaching of nutrients, especially the water-soluble nutrients from it. MBD can be used along with live feeds in a hatchery's larval rearing of different fish species. Co-feeding of these live feeds and MBD can be the best solution in the larvae culture of fish. The MBD feed can be on-size or crumbled. The on-size MBD can be microextruder marumerization (MEM), and particle assisted rotational agglomeration (PARA). MEM is the most common type of MBD, and this idea has been adopted from the pharmaceutical industry. The cold extruded feed gets spheroid shape in the marumerizer, which helps in forming a smooth layer outside the MBD. Since these feed particles are not encapsulated, there is may be a chance of leaching water-soluble nutrients from the feed. It is most suitable for freshwater and marine fish larvae, but it is not suitable for the column feeding fish larvae. The advantages and the disadvantages of use of MBD in larval rearing of fish with a view to replace the feeding of live feeds are briefly described in this article.